Design and Creation of a Profile Catalog of MSMEs Assisted by PT. Pertamina Hulu Rokan, Mandau Region and others - Mubarak, Husni; Maulana, Hutomo Atman; Astuti, Dwi (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2024)
The current problem is that many small and medium MSMEs are not touched by technology and do not have valid information regarding their business profiles or information about what products are offered to the market. This activity is a simple effort to overcome MSME problems, one of which is by presenting profiles and business catalogs from the MSMEs themselves. In accordance with the assignment mandated by PT partners. PHR hopes that its fostered MSMEs in Mandau District and its surroundings. The main goal is to have a positive influence on MSMEs and others by equipping them with something that is up great. Creating MSME Profiles with complete Business Catalog designs both in digital and paper-based forms. Guan to increase the capacity of MSMEs, competitive in the long term. This community service activity was carried out on MSMEs fostered by PT Pertamina Hulu Rokan (PHR) in Mandau District and its surroundings.